The well-being of Chinese older adults : application of the person-environment fit theory - Ouyang, Zheng (Cambridge Scholars Publishing, 2018)
The well-being of the Chinese elderly has recently drawn the attention of a significant number of researchers. This book examines the relationship among personal factors (such as age, sex, income, cognitive functioning, and functional disability), environmental factors (including satisfaction of housing, community, safety, and transportation), person-environment fit, well-being, and the mediating effects of supplementary fit. It represents the first study to integrate the concepts of complementary fit (needs supply) and supplementary fit (value congruence) in one theoretical framework, explori.